PENGARUH PENAMBAHAN AMMONIUM SULFAT (NH4)2SO4 DAN WAKTU PERENDAMAN BUFFER FOSFAT TERHADAP PEROLEHAN CRUDE PAPAIN DARI DAUN PEPAYA (CARICA PAPAYA, L) - Mitha Alviyulita; Pinta Rizki Mala Hasibuan; Farida Hanum (Talenta Publisher (Universitas Sumatera Utara), 2014)
Papaya leaves is a plant that rich in benefits. Papaya leaves contains papain enzyme which is a protease enzyme that very helpful for the industry. This study aims to determine the effect of the saturation level of ammonium sulphate (NH4)2SO4 and immersion time with phosphate buffer to get yield of protease from crude papaya. In this study varied immersion time with phosphate buffer is 0, 12, 24, and 36 hours and the saturation level of ammonium sulphate (NH4)2SO4 is 40, 50, 60, 70, 80, and 90 %. Analysis of protease activity was performed using UV spectrophotometer to measure the wavelength and absorbance values​​. The highest value of the protease activation (132,98% unit/ml) was obtained during 36 h of immersion time in phosphate buffer with 60% concentration of ammonium sulphate (NH4)2SO4. The results found on 36 h of immersion time in 90% of ammonium sulphate concentration were the highest for rendement and water content value of 37,62 and 65,70%, respectively.